Vaccines for Perinatal and Congenital Infections—How Close Are We? - Singh, Tulika; Otero, Claire E.; Li, Katherine; Valencia, Sarah M.; Nelson, Ashley N.; Permar, Sallie R. (Frontiers in Pediatrics, 2020)
Congenital and perinatal infections are transmitted from mother to infant during pregnancy across the placenta or during delivery. These infections not only cause pregnancy complications and still birth, but also result in an array of pediatric morbidities caused by physical deformities, neurodevelopmental delays, and impaired vision, mobility and hearing. Due to the burden of these conditions, congenital and perinatal infections may result in lifelong disability and profoundly impact an individual’s ability to live to their fullest capacity. While there are vaccines to prevent congenital and perinatal rubella, varicella, and hepatitis B infections, many more are currently in development at various stages of progress. The spectrum of our efforts to understand and address these infections includes observational studies of natural history of disease, epidemiological evaluation of risk factors, immunogen design, preclinical research of protective immunity in animal models, and evaluation of promising candidates in vaccine trials. In this review we summarize this progress in vaccine development research for Cytomegalovirus, Herpes simplex virus, human immunodeficiency virus, Toxoplasma, Syphilis, and Zika virus congenital and perinatal infections. We then synthesize this evidence to examine how close we are to developing a vaccine for these infections, and highlight areas where research is still needed.